THE CONCEPT AND CONTEXT OF ISLAMIC EDUCATION LEARNING IN THE DIGITAL ERA: RELEVANCE AND INTEGRATIVE STUDIES - Amirotu Diana; Mohammad Zakki Azani; Mahmudulhassan M (Profetika: Jurnal Studi Islam, 2024)
The digital age has brought great changes in the world of Islamic religious education. Educational activities become more effective and efficient with the presence of digital devices. In learning activities, it is hoped that a community will be formed that can utilize digital devices or media to encourage the creation of quality learning and accommodate the potential and participation of students. The purpose of this study is to analyze the relevance of Islamic education in the digital era. The method used in this research is in the form of literature studies, and the form of qualitative research. The results of the study found that the era of globalization has had a significant impact on Islamic education, including first, along with the increasingly sophisticated technology, it is easier to obtain various types of information. The task of national education in the era of globalization places great emphasis on the value system and philosophy, where the philosophy of Islamic education is the concept of thinking about education based on Islamic religious teachings regarding the nature of human abilities so that they can be developed and guided to become human beings whose entire personality is imbued with Islamic teachings. Second, the pressures of globalization place a qualified, educated and skilled workforce. Third, collaboration in schools is very important, especially the influence of globalization and international cooperation in the field of education. Thus, the relevance-integration of the concept and context of Islamic studies with the era of globalization is very important as an effort to appreciate the worldview of the dynamics and progress of education in the era of globalization.